2018
DOI: 10.1088/1361-6501/aaeab8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple contacts investigation of single silicon nanowires with the active voltage contrast scanning electron microscopy technique

Abstract: A method for analysing the formation of electrical contacts to single silicon nanowires (Si NWs) by exploiting scanning electron microscopy (SEM) images, using active secondary electrons voltage contrast, is presented. Our approach clearly demonstrates the advantages of the proposed technique in analysing multiple contacts to a single nanowire simultaneously, in comparison to the conventional voltage contrast technique, where only two contact structures can be analysed, mainly for studies of the material dopan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The study has also shown that the PVP-coated part of the AgNWs could be distinguished using the voltage contrast . The voltage contrast is also used to observe other nanowire materials such as Si nanowires and composites comprising carbon nanotubes and insulating polymers. , …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The study has also shown that the PVP-coated part of the AgNWs could be distinguished using the voltage contrast . The voltage contrast is also used to observe other nanowire materials such as Si nanowires and composites comprising carbon nanotubes and insulating polymers. , …”
Section: Introductionmentioning
confidence: 94%
“…The study has also shown that the PVP-coated part of the AgNWs could be distinguished using the voltage contrast. 23 The voltage contrast is also used to observe other nanowire materials such as Si nanowires 24 and composites comprising carbon nanotubes and insulating polymers. 25,26 In the case of metallic nanowires with concentrations close to the percolation threshold, the degree of charging of nanowires by irradiation of PEs may differ for the isolated nanowires and nanowires in contact with the conductive network.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation